Effects of inoculation amount and application method on the biodrying performance of municipal solid waste and the odor emissions produced. (15th June 2019) - Yuan, Jing; Zhang, Difang; Ma, Ruonan; Wang, Guoying; Li, Yun; Li, Shuyan; Tang, Huan; Zhang, Bangxi; Li, Danyang; Li, Guoxue
Highlights: Mixing in 5% inoculation material improved biodrying of municipal solid waste. Covering the pile with inocula yielded the highest water content reduction. All additions of inoculation material to the pile enhanced cellulose degradation. 10% inoculation material reduced the NH3 emissions by 39.1–54.3%. The covering method of inoculation material reduced 65.1% H2 S emission. Abstract: The effects of inoculation amount and application method on the biodrying of municipal solid waste (MSW) was investigated in this study. Results showed that a low level (5%) of inoculation with mature compost significantly improved the biodrying index (4.96), while adding greater amounts decreased the biodrying performance by increasing the volatile solid degradation rate. Covering the pile with inoculation material resulted in the highest water removal (72.7%) and greatest water content reduction (from 60.2% to 17.7%). Meanwhile, first covering and then incorporating the inoculation material into the biodrying pile did not improve biodrying performance. Clearly, addition of varying amounts of inoculation material via different application methods enhanced cellulose degradation rates by 2.3–14.2%. Using 10% inoculation material reduced the NH3 emissions by 39.1–54.3% regardless of inoculation method, inoculation amount had a greater effect on NH3 emissions than that of inoculation method. The covering inoculation material could reduce 65.08% H2 S emission, the inoculation method had a greater effect on H2 S emissions than that of inoculation amount. Given the comprehensive considerations of emission reduction and biodrying performance, a covering of 10% inoculating material is a suitable approach to improve biodrying performance and mitigate odorous gases emissions.